THE BACKGROUND OF THE LEGEND OF THE“FEATHER ROBE PINE” OF THE TOYO RIVER, AICHI PREFECTURE, JAPAN - Shirai, Katsuhisa (Universitas Negeri Surabaya, 2025)
This study examines the legend of the “Feather Robe Pine” of the Toyo River, Aichi Prefecture, Japan, with the aim of clarifying the background of its formation and the characteristics of its transmission. Based on the archival analysis, the following insights were derived. As a result, four points were clarified. First, the background of the “Feather Robe Pine” legend preserved of the Toyo River is believed to have involved the prayers of the people in Toyo River basin for flood control. Second, a connection can be recognized between the legend of the “Feather Robe Pine” of the Toyo River and the Hoshino clan, whose influence extended into the Toyokawa River basin during the Muromachi period, held the position of “Role of the Heavenly Feather Robe” in the Daijosai ceremony. Third, the “Feather Robe Pine” legend of the Toyo River is connected to the story of the noblewoman and the “Single Leaf Tea Garden” preserved in Gyomei-cho. Fourth, the “Feather Robe Pine” legend of the Toyo River is considered to have been intricately constructed under the influence of the “Feather Robe Pine” legend of Miho no Matsubara.